Deformation behavior of aluminum pillars produced by Xe and Ga focused ion beams: Insights from strain rate jump tests. (5th November 2019) - Xiao, Y.; Maier-Kiener, V.; Michler, J.; Spolenak, R.; Wheeler, J.M.
Abstract: Micro-compression testing of focused ion beam fabricated pillars is a popular technique for mechanical characterization at small scales. However, there are concerns associated with these ion-prepared samples, including irradiation damage from Ga ions and Ga segregation at grain boundaries resulting in liquid metal embrittlement. In this work, this is investigated using strain rate jump nanoindentation and micro-compression of single crystalline and ultrafine-grained aluminum with different grain boundary conditions. The extracted strain rate sensitivity and activation volume are used to study the effects of Ga and Xe ion species from fabrication and testing methods on deformation behavior of aluminum samples. Results show that the measured strain-rate sensitivity of non-equilibrium, ultrafine-grained aluminum is significantly affected by the dosage of Ga. Activation volumes suggest that the dominant deformation mechanism remains consistent despite Ga at the boundaries. Atom probe tomography reveals that Ga was observed to segregate to aluminum grain boundaries up to 2.2 at.% in the FIB prepared sample. Graphical abstract: Unlabelled Image Highlights: The deformation of single- and poly-crystalline Aluminum was studied by strain rate jump nanomechanical testing. Higher strain rate sensitivity was observed in high pressure torsion Al with increasing Ga dose from FIB preparation. Activation volumes of all Al samples remain largely consistent among all testing methods and Ga exposure. Observed Ga grain boundary segregation of up to 2.2 at% was found by APT, while no Ga was detectable by TEM analyses.